NONVERBAL COMMUNICATION OF A CHILD WITH DOWN SYNDROME IN THE EARLY AGE - Homolková, Kamila (Bohemica Olomucensia, 2021)
This article examines the significant role of nonverbal communication in typically developing children and children with Down syndrome as well. The speech development in this part of population is delayed and because of that it is powerful to use the methods of augmentative or alternative communication with them, e.g. the sign systems. Thanks to this the children are able to achieve the communication success earlier, moreover motor skills and cognitive functions are positively developed. One part of this article is a case study of a nonverbal communication of a boy with Down syndrome and his specific means of communication are introduced.
Keywords: alternative and augmentative communication; Down syndrome; intellectual disability; nonverbal communication